Identification of Platelet Inhibitor Present in the Melon (Cucurbitacea Cucumis Melo) - Altman, Raul; Rouvier, Jorge; Weisenberger, Hans (Thrombosis and Haemostasis, 1985)
An active fraction was isolated from an aqueous melon extract (Cucurbitacea cucumis melo) and was shown that it inhibits human platelet aggregation induced by epinephrine, ADP, collagen, thrombin, sodium arachidonate, prostaglandin endoperoxide analogue U-46619 and PAF-acether. Identification of the active substance as adenosine was indicated by TLC which gave identical Rf value compared to adenosine, by the UV spectrum, because the inhibitory effect on platelet aggregation disappeared after the addition of adenosine-deaminase and because the substance under study and adenosine produced the same spectra in the mass spectroscopy.
Keywords: Platelet aggregation; Adenosine; Inhibitor